Reward as a motivator for Quran memorization: A Skinnerian perspective - Nasution, Nayla Afna Sa'adah; Sa’diyah, Elok Halimatus (Institut Agama Islam Negeri Langsa, 2024)
The phenomenon of implementing rewards in the memorization of the Quran provides new insights into how positive reinforcement can enhance motivation and sustain the process of memorization (tahfidz), in alignment with Skinner's theory. This literature study aims to detail how rewards can serve as motivational tools within the progression of Quran memorization. The research employs a qualitative method with a literature study approach. The research steps include determining keywords, searching for articles using Publish or Perish, and filtering relevant articles according to predetermined criteria. A review of six selected articles serves as the object of this study, utilizing thematic data analysis to examine the application of rewards in Quran memorization based on Skinner's theoretical framework. The findings of this literature review indicate that: 1) Skinner's concept of rewards is effective in reinforcing positive behavior through positive reinforcement. The implementation of rewards can also encourage the development of intrinsic motivation, reducing reliance on extrinsic motivation. 2) The provision of verbal and non-verbal rewards effectively enhances motivation and memorization of the Quran. Rewards such as praise or tangible gifts can invigorate the learning spirit, provided they are administered wisely in order to maintain sincere intentions in memorization. 3) Existing research demonstrates that the application of rewards based on Skinner's theory effectively strengthens the habit of memorizing the Quran, thereby facilitating the formation of routines and reinforcing an individual's commitment to achieving memorization targets. Future research is recommended to utilize quantitative or qualitative methods to further examine the application of rewards in enhancing Quran memorization motivation.